Carrier frequency offset and time synchronization estimation based on new autocorrelation over fading channel - WANG Yong; LIAO Gui-sheng; WANG Xi-yuan (Tongxin xuebao)
A kind of carrier frequency offset estimation algorithm was brought forwards that could be applied in frequency selective fading channel for the multi-antenna system.The algorithm used the given training sequences,assisted-data method to estimate frequency offset and new self-correlation definition to fulfill time synchronization.It was not sensitive to clock synchronization error,and could work under multiple sampling rates.Moreover,it was easy to be realized and had high precision.